THE DYNAMICS OF EU COUNTRIES DEBT IN THE CONTEXT OF THE GLOBAL COVID-19 PANDEMIC - Nikolaieva , D.S.; Yakubovskiy , S.O. (The actual problems of regional economy development, 2023)
The article examines the debt situation in European countries, especially in Italy and Spain, since these countries are leaders among European countries in terms of debt burden. The article examines both external and public debt, but more attention is paid to public debt, as it is more important than external debt for Italy and Spain. This situation is related to the fact that both countries are members of the European Union and the Eurozone, that is, they pay their foreign debt in euros, and the national currency is also the euro, which gives the countries more favorable conditions. For comparison with the countries of the euro zone, the article also examines the debt situation in Poland, since this country has kept its own currency, and for its economy the external debt is no less significant than the national debt. The debt situation in the countries is analyzed for the period from 2016 to 2021 and the beginning of 2022, since this period of time allows to assess the situation before and during the pandemic. According to the data analysis, Poland has the smallest public debt in 2021, and Greece has the largest, the article also examines such indicators as the yield of 10-year bonds of the countries, the public deficit and the foreign debts of Italy, Spain and Poland. In 2021, among the countries with the highest yield of 10 summer government bonds, Poland is leading, and in 2022, the country has the highest yield, this situation indicates the growth of risks for the country's economy and its stability. The largest increase in the government deficit in 2020 occurred in Italy, while the smallest in Poland. Regarding public debt, the situation is the same, the public debt of Italy in 2020 increased by 29.5%, Spain by 27%, and Poland by 13.9% of GDP. In the article, vector autoregressions were constructed to reveal the presence of dependence between budget deficits and current accounts of the balance of payments of the countries under study. The results of the modulation proved that there is such a dependence in Spain, which was also confirmed by linear regression and the indicators were found to be inversely related. The modulation results also proved the presence of an inverse relationship between the yield on the 10-year Spanish government bond and the current account. In Italy and Poland, the existence of a double deficit was not detected.